2018
DOI: 10.1177/1558944718812161
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use in Hand Surgery: Surgeon Decision Making and Adherence to Available Evidence

Abstract: Background: There are no clearly defined guidelines from hand surgical societies regarding preoperative antibiotic prophylaxis. Many hand surgeons continue to routinely use preoperative prophylaxis with limited supporting evidence. This study aimed to determine for which scenarios surgeons give antibiotics, the reasons for administration, and whether these decisions are evidence-based. Methods: An anonymous 25-question survey was e-mailed to the 921-member American Society for Surgery of the Hand listserv. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Future tracer data may show a decline in the usage of antibiotics. 64 Clear guidelines remain to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Future tracer data may show a decline in the usage of antibiotics. 64 Clear guidelines remain to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Patients prescribed antibiotics unnecessarily may have drug or allergic reactions or may develop other infections, such as pseudomembranous colitis due to C. difficile. 8 A previous prospective study of 149 consecutive patients undergoing open reduction and internal fixation of a closed ankle fracture showed no significant…”
Section: Introductionmentioning
confidence: 94%
“…Patients prescribed antibiotics unnecessarily may have drug or allergic reactions or may develop other infections, such as pseudomembranous colitis due to C. difficile . 8 …”
Section: Introductionmentioning
confidence: 99%
“…The survey demonstrated that 5% of surgeons did not prescribe preoperative antibiotics for any procedures, including those that involved imbedded hardware. 1 This study demonstrated that the use of preoperative antibiotics is random and not standardized.…”
mentioning
confidence: 90%